2016
DOI: 10.1136/gutjnl-2015-311019
|View full text |Cite
|
Sign up to set email alerts
|

Role of bismuth in improvingHelicobacter pylorieradication with triple therapy

Abstract: In most regions of the world, antimicrobial resistance has increased to the point where empirical standard triple therapy for Helicobacter pylorieradication is no longer recommended. The treatment outcome in a population is calculated as the sum of the treatment success in the subpopulation with susceptible infections plus treatment success in the subpopulation with resistant infections. The addition of bismuth (i.e., 14-day triple therapy plus bismuth) can improve cure rates despite a high prevalence of antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
254
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(278 citation statements)
references
References 108 publications
9
254
0
15
Order By: Relevance
“…We showed that the Niu transporter is additionally involved in cobalt uptake, while the NixA permease is not, although the latter belongs to the NiCoT family. Bismuth, a metal that is not a natural protein cofactor, is a component of the new Pylera medication, in combination with two antibiotics and a proton pump inhibitor [64]. Pylera has proven to be more efficient in eradicating H .…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the Niu transporter is additionally involved in cobalt uptake, while the NixA permease is not, although the latter belongs to the NiCoT family. Bismuth, a metal that is not a natural protein cofactor, is a component of the new Pylera medication, in combination with two antibiotics and a proton pump inhibitor [64]. Pylera has proven to be more efficient in eradicating H .…”
Section: Discussionmentioning
confidence: 99%
“…The recommended eradication regimen in Northern Europe is triple therapy with a PPI in combination with clarithromycin and amoxicillin or metronidazole for 7 days [5]. A treatment alternative with comparable efficacy is bismuth-containing quadruple therapy, since the addition of bismuth can lead to a 30-40% increase in eradication success in areas with high antibiotic resistance [6]. However, bismuth is rarely used in Sweden, and many other combinations of antibiotics can also be prescribed [5].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment outcome in a population is based on the following formula: (% success with susceptible strains) + (% success with resistant strains) = overall eradication rate (Dore et al, 2016). The eradication rates of different regimens (14-day triple therapies, sequential therapies, concomitant therapies, BQTs, levofloxacin triple therapies or 7-day vonoprazan triple therapies) are greater than 95% in subpopulations with susceptible infections.…”
Section: Treatmentmentioning
confidence: 99%